Pensadores dos barracos: enunciado e estilo do grupo facção central em perspectiva dialógica - Barbosa, Edilberto de Oliveira (2023)
In the mid-1980s, Brazil closed, at least apparently, the chapter in its history that began with the 1964 Military Coup. Redemocratization brings with it, or revives, the discourse of human rights, not just as hope, since it that effectively articulate the political forces responsible for drafting the 1988 Constitution, called the “Citizen Constitution”, which, in the words of Bresser-Pereira, consolidates the country as a democracy by establishing universal suffrage and guaranteeing civil rights. Furthermore, the constituents, going beyond the minimum concept of democracy, “wanted the Brazilian State to also be a social State, and, in addition to guaranteeing civil and political rights, they introduced an extensive number of social rights into the constitutional text” (2021, p.298). However, when approved, on October 5, 1988, the political pact that had generated it had already collapsed and the dominant neoliberalism since then and throughout the 1990s rejected it, among other reasons, for its social nature. It is in this context that rap – understood here as a discourse genre –, one of the manifestations of the hip hop movement and/or culture, is consolidated in the city of São Paulo as an urban popular music associated with the poorest black populations on the outskirts of the city. The purpose of this song would not be limited to leisure, but also to active political participation, and, in its version or style considered to be more radical, the socalled gangsta rap, it is common to consider that the lyrics have preeminence in relation to the sound aspect, and that the purpose of protest eliminates that of leisure. The marked presence of a social discourse of inclusion in recent decades has not meant that this music, which was censored in the late 1990s, is naturally debated and circulates freely in all spheres of society, although it is known by young people from all the peripheries of the country, which seems to be an indication that it continues to be stigmatized, due to its thematic content, style of language, form of production, social origin or other reasons. In this research, we propose to analyze statements by one of the main rap artists in the country since the 1990s, the group Facção Central, in order to understand their style, which is to say: how these artists represent themselves, in their works, and how they represent men and social relations. From a conception of language as a creation and reflection of social life, which plays in the organization of social life, through discursive communication, a decisive role for its organization, in its various spheres, and for the very possibility of existence of a human consciousness and culture, and considering, with Bakhtin and the Circle, that both language integrates life, and life enters language, through concrete statements (2019, p.17), we will take the perspective analysis of dialogic discourse analysis, based on the concepts of ideological sign, enunciation, discourse genres, style to answer the questions: 1. How does the speaker (author) construct his own image in music? 2. What image does the speaker (author) construct of the addressee? 3. What image does the speaker (author) construct of the character and the relationships that he and the addressee have with this character? 4. What are the general style characteristics in the utterances of the Facção Central group? The few studies that have addressed the group's work so far have left unsatisfactory explanations for both the linguistic materiality of the songs and the problem of the recurrence of scenes of violence. Our hypothesis is that the analysis of the linguistic style of the utterances can bring new elements for a better understanding of the verbal and extraverbal aspects of the utterance, providing a safer basis for further research that will certainly be done, given the complexity of the work, which, more recently, it went beyond the popular music genre and entered the field of essays. We will proceed with the analysis of three utterances-songs published between 1999 and 2001, considering that the material of the rap utterance-song is the sound and the word, and that the latter has its verbal and extraverbal aspect, and that the essence is both social both the sound and the word